High reward makes items easier to remember, but harder to bind to a new temporal context - Madan, Christopher R.; Fujiwara, Esther; Gerson, Bridgette C.; Caplan, Jeremy B. (Frontiers in Integrative Neuroscience, 2012)
Learning through reward is central to adaptive behaviour. Indeed, items are remembered better if they are experienced while participants expect a reward, and people can deliberately prioritize memory for high- over low-valued items. Do memory advantages for high-valued items only emerge after deliberate prioritization in encoding? Or, do reward-based memory enhancements also apply to unrewarded memory tests and to implicit memory? First, we tested for a high-value memory advantage in unrewarded implicit and explicit tests (Exp 1). Participants first learned high or low reward values of 36 words, followed by unrewarded lexical decision and free recall tests. High-value words were judged faster in lexical decision, and more often recalled in free recall. These two memory advantages for high-value words were negatively correlated suggesting at least two mechanisms by which reward value can influence later item-memorability. The ease at which the values were originally acquired explained the negative correlation: People who learned values earlier showed reward effects in implicit memory while people who learned values later showed reward effects in explicit memory. We then asked whether a high-value advantage would persist if trained items were linked to a new context (Exps 2a,b). Following the same value training as in Exp 1, participants learned lists composed of previously trained words mixed with new words, each followed by free recall. Thus, participants had to retrieve words only from the most recent list, irrespective of their values. High- and low-value words were recalled equally, but low-value words were recalled earlier than high-value words and high-value words were more often intruded (proactive interference). Thus, the high-value advantage holds for implicit and explicit memory, but comes with a side effect: High-value items are more difficult to relearn in a new context. Similar to emotional arousal, reward value can both enhance and impair memory.